Laminar Composites - Staab, George (Elsevier, 1999)
This text provides students with the theoretical knowledge and practical skills necessary to identify, model, and solve structural analysis problems. The material is illustrated throughout with numerous diagrammatic examples, as well as example problems similar in nature to those found in lower level strength of materials texts. The difficulty of the examples and problems varies from simple to complex. A solutions manual is available for lecturers who adopt the book for classroom teaching.